Strategies of Arabic Language Teachers Using Instructional Media and Technology to Improve Students’ Reading Skills - Dasep Bayu Ahyar; Riyan Haqi Khoerul Anwar; Zaenur Ropiq (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
The development of instructional media and learning technologies requires Arabic language teachers to adapt relevant teaching strategies in order to enhance students’ language skills, particularly reading ability (al-qirā’ah). This study aims to analyze and describe the strategies employed by Arabic language teachers in utilizing instructional media and learning technologies to improve students’ reading skills at MTs YPPA Cipulus. The study adopts a qualitative method with a case study approach, selected to obtain an in-depth understanding of teachers’ practices, challenges, and pedagogical considerations in the use of instructional media and learning technologies. The findings indicate that teachers employ instructional media in an adaptive manner, including the use of the online platform MTS Arabic, which is subsequently converted into printed teaching materials due to limited facilities and school policies that prohibit students from using digital devices. These conditions arise from constraints in technological infrastructure and students’ low levels of digital literacy, despite teachers’ efforts to enhance their competencies through artificial intelligence (AI)-based technology training. This study concludes that the utilization of instructional media and learning technologies remains at the level of teacher readiness and has not yet been optimally implemented in instructional practice. Nevertheless, there is considerable potential to improve the effectiveness of reading instruction through the strengthening of infrastructure and the adoption of more adaptive school policies that support the gradual integration of technology.